2011
DOI: 10.1063/1.3626837
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous onset of magnetic reconnection in toroidal plasma caused by breaking of 2D symmetry

Abstract: Magnetic reconnection is studied in the collisionless limit at the Versatile Toroidal Facility (VTF) at MIT. Two distinct magnetic configurations are applied in the experiments; an open magnetic cusp and a closed cusp. In the open cusp configurations, the field lines intersect the the vacuum vessel walls and here axisymmetric oscillatory reconnection is observed. Meanwhile, in the closed cusp configuration, where the field lines are confined inside the experiment, the coupling between global modes and a curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Similar potential structures have been measured in laboratory experiments by Egedal et al [], who showed that a current system is set up in the reconnection region, where ion polarization currents perpendicular to B are closed by parallel currents carried by electrons close to the X line. Investigating the physics behind these potentials, Egedal et al [] showed that a combination of magnetic and electric trapping of electrons can explain the formation of the potential structures and that these are responsible for the anisotropic electron pressure that has been observed in reconnection regions both in the magnetotail and in laboratory experiments.…”
Section: Theoretical Motivationsupporting
confidence: 79%
“…Similar potential structures have been measured in laboratory experiments by Egedal et al [], who showed that a current system is set up in the reconnection region, where ion polarization currents perpendicular to B are closed by parallel currents carried by electrons close to the X line. Investigating the physics behind these potentials, Egedal et al [] showed that a combination of magnetic and electric trapping of electrons can explain the formation of the potential structures and that these are responsible for the anisotropic electron pressure that has been observed in reconnection regions both in the magnetotail and in laboratory experiments.…”
Section: Theoretical Motivationsupporting
confidence: 79%
“…In the solar wind, a long extended X‐line of over hundreds of RE has also been reported (Phan et al, ). Laboratory experiments such as the Magnetic Reconnection Experiment (Dorfman et al, , ) and the Versatile Toroidal Facility (Egedal et al, ; Katz et al, ) have also observed X‐line spreading across the device.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, experimental and satellite observations of systems with a strong guide field reveal strikingly different behavior of X‐line spreading. For example, experiments performed at the versatile toroidal facility (VTF) [ Katz et al , 2010; Egedal et al , 2011] exhibit reconnection beginning in a localized region and spreading bidirectionally in the out‐of‐plane (toroidal) direction at a speed consistent with the Alfvén speed based on the guide field. Another example is bidirectional spreading (or elongating) of ribbons observed during two‐ribbon solar flares [ Qiu , 2009], including the Bastille Day flare [ Qiu et al , 2010].…”
Section: Introductionmentioning
confidence: 99%